The psychological novel and a trilateral comparison: Colette, Evgenia Dimitrova, and Hortensia Papadat-Bengescu (Colloquia Comparativa Litterarum, 2025)
The novel of the first half of the 20th century, modern and modernist across much of Europe, intertwines newly developed scientific ideas about the depths of the human psyche with a newly emerging sense of threat posed by uncontrollable human instincts and, consequently, by fluctuations in the behaviour of the characters. This type of psychological novel also reflects a philosophical perspective on subjective human time and focuses on particular narratological techniques. The article outlines the characteristics of the psychological novel and the specific writing techniques that enable an exploration of the depths of the human psyche. Examples have been drawn from the works of three writers from different European countries: Colette, Evgenia Dimitrova, and Hortensia Papadat-Bengescu.
Keywords: 20th century psychological novel; narrative techniques; Colette; Evgenia Dimitrova; Hortensia Papadat-Bengescu